Screening for Carpal Tunnel Syndrome Using Daily Behavior on Mobile Devices - Watanabe, Takuro; Xia, Chengshuo; Fujita, Koji; Sugiura, Yuta (Computer (Long Beach, Calif.), 2023)
Our vision is to detect hand disorders through daily behaviors so that people can unconsciously perform screening for the disorders without any additional actions being needed. To realize this vision, we employed mobile devices and focused on screening using two types of daily behaviors: writing and mobile game manipulations.